2015
DOI: 10.1111/apa.13222
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards the resuscitation of periviable infants: a national survey of American Muslim physicians

Abstract: American Muslim physicians have high rates of support for delivery room resuscitation of periviable infants. Their intended behaviour appears to associate with religious values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 25 publications
(23 reference statements)
1
24
1
Order By: Relevance
“… confirmed the association between the personal importance of religion and a preference for prolonging life even in situations where there were gloomy prospects for unimpaired survival. This appears to be a consistent finding both when physicians and lay people are surveyed. Switzerland does not just have four official languages; it is also religiously diverse, with equal shares of Protestants and Catholics, as well as sizable Muslim and Jewish communities.…”
supporting
confidence: 71%
See 2 more Smart Citations
“… confirmed the association between the personal importance of religion and a preference for prolonging life even in situations where there were gloomy prospects for unimpaired survival. This appears to be a consistent finding both when physicians and lay people are surveyed. Switzerland does not just have four official languages; it is also religiously diverse, with equal shares of Protestants and Catholics, as well as sizable Muslim and Jewish communities.…”
supporting
confidence: 71%
“…As in similar polls conducted elsewhere (6,8), the respondents in the Hendriks et al study (5) only comprised a minorityless than 24%of those surveyed. The views of the population at large may be quite different from the answers given by the men and women who actively participate in surveys.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Bonnie Arzuaga et al report the results of a survey of a group of Muslim physicians in the United States about their attitudes towards resuscitating periviable infants. The survey showed that there was high rates of support for delivery room resuscitation of periviable infants.…”
Section: How American Muslim Physicians Feel About Resuscitating Perimentioning
confidence: 99%
“…The inability to predict the individual outcome of an infant born at the threshold of viability has led to variations in the treatment offered and provided to extremely premature infants in different countries (1)(2)(3)(4)(5)(6)(7)(8). Cultural differences, including different perceptions on the quality of life, sanctity of life and the acceptance of comfort care as an option, also influence medical practice (1)(2)(3)(4). These issues may explain some of the differences between the national guidelines for perinatal care in the Netherlands and the United States.…”
Section: Introductionmentioning
confidence: 99%